POTENSI FOOD LOSS DAN FOOD WASTE PADA UMKM: MFCA, NUDGING DAN NEUTRALIZATION THEORY - Taufika Nurani Fajri; Elvia R. Shauki (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This research analyzes the food loss and food waste phenomenon at Warung Tegal in Bekasi City where food loss and food waste dominate in landfill resulted in overload capacity. Warteg did not know about food loss and food waste ‘s potential, so it was ignored. The analysis was carried out to calculate the potential for food loss and food waste generation using material flow cost accounting (MFCA) from 6 Warteg units and using neutralization and nudge theory to see the behavior of Warung Tegal in management. Case study research strategy with observation and interview research instruments using primary data. The results showed that Warteg A produced a FLW of 10.57%, equivalent to Rp. 568,855. Warteg has not carried out optimal management of neutralization through 3 (three) neutralization techniques: denial of responsibility, denial of injury, and appear to higher loyalty. Warteg minimally mitigates food loss and food waste through nugding carried out upstream and downstream.